2007
DOI: 10.1002/hep.21724
|View full text |Cite
|
Sign up to set email alerts
|

Natural history and disease progression in Chinese chronic hepatitis B patients in immune‐tolerant phase†

Abstract: In view of the findings that high hepatitis B virus (HBV) deoxyribonucleic acid (DNA) is associated with increased risk of chronic hepatitis B (CHB)-related complications, disease progression in CHB patients in the immune-tolerant phase is uncertain. We evaluated disease progression in 57 immune-tolerant CHB patients with high HBV DNA. Each subject underwent an initial liver biopsy. In those who remained in the immune-tolerant phase, a follow-up liver biopsy was performed after 5 years of follow-up. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
151
3
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(168 citation statements)
references
References 40 publications
11
151
3
3
Order By: Relevance
“…Individuals with perinatal acquisition of HBV typically have a prolonged immunetolerant phase that can last up to three decades. A 5-year follow-up study of individuals who remain in the immunetolerant phase showed no or minimal disease progression [29]. In natural history studies of Asian HBsAg-positive children, the rate of spontaneous HBeAg seroconversion is low: \2% per year among children 3 years or younger and 4-5% per year in older children [30].…”
Section: Natural Course Of Disease and Hbeag Seroconversionmentioning
confidence: 99%
“…Individuals with perinatal acquisition of HBV typically have a prolonged immunetolerant phase that can last up to three decades. A 5-year follow-up study of individuals who remain in the immunetolerant phase showed no or minimal disease progression [29]. In natural history studies of Asian HBsAg-positive children, the rate of spontaneous HBeAg seroconversion is low: \2% per year among children 3 years or younger and 4-5% per year in older children [30].…”
Section: Natural Course Of Disease and Hbeag Seroconversionmentioning
confidence: 99%
“…The liver disease activities are low in this phase despite active HBV replication [9]. A recent report from Hong Kong indicated that adult HBV carriers who remain in the immune tolerance phase have minimal disease progression [10]. After 2-3 decades of persistent infection, chronic hepatitis B enters the second immune clearance phase.…”
Section: Natural Course Of Chronic Hepatitis Bmentioning
confidence: 99%
“…A study conducted by Hui et al 10 revealed that elevated levels of ALT are taken as a marker for immune clearance and used as predictive measure to evaluate the progression of disease. According to the guidelines given by AASLD, the patients with HCV infection need to be monitored by every 3 months during their first year to verify them as inactive carrier of HCV 11 .…”
Section: Reactivation Of Virusmentioning
confidence: 99%